Lewis Mayer, The Baltimore City Code: Comprising the Statutes and Ordinances Relating to the City of Baltimore 589 (1879) - (:unkn) unknown (My University, 1879)
Art. 20, sec. 53 § 63: All gunpowder brought within the limits of the city by land, or into the port or harbor, in any ship or vessel, other than a ship or vessel of war, shall be stored in the said magazine as aforesaid; if brought by land as aforesaid, within seventeen hours thereafter; if brought into the port or harbor as aforesaid, within forty-eight hours after the ship or other vessel thus bringing it shall have broken bulk; proved the quantity thus brought in shall exceed the weight of one quarter barrel as above defined
Keywords: GUNPOWDER - TRANSPORTATION